THE INFLUENCE OF HUMAN RESOURCE QUALITY, PERFORMANCE EVALUATION AND INCENTIVES FOR EMPLOYEE PRODUCTIVITY PT. BANDAR AGUNG PERKASA MEDAN - Agnes Ilfani Ndruru; Lenny Menara Sari Saragih; Andriasan Sudarso; Sipur (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research method is quantitative by distributing questionnaires. The population in this study were all employees at PT. Bandar Agung Perkasa Medan and the sampling technique used the census method because the population was less than 100 people. The data analysis technique used the classical assumption test, multiple linear regression analysis, t-test, f-test and coefficient of determination. The results of the study indicate that partially the quality of human resources, performance evaluation and incentives have a positive and significant effect on employee productivity. Simultaneously, the quality of human resources, performance evaluation and incentives have a positive and significant effect on employee productivity. The magnitude of the determination coefficient of 0.811 means that the ability of the human resource quality variables, performance evaluation and incentives on employee productivity is 81.1%, while the remaining 18.9% are other variables that were not studied. In conclusion, partially and simultaneously the quality of human resources, performance evaluation and incentives on employee productivity at PT. Bandar Agung Perkasa.